Application of tangent-arc technology for deep inspiration breath-hold radiotherapy in left-sided breast cancer - Li, Yucheng; Zhan, Wenming; Jia, Yongshi; Xiong, Hanchu; Lin, Baihua; Li, Qiang; Liu, Huaxin; Qiu, Lingyun; Zhang, Yinghao; Ding, Jieni; Fu, Chao; Chen, Weijun (Frontiers in Oncology, 2023)
【Abstract】 Objective To explore the advantages of dosimetry and the treatment efficiency of tangent-arc technology in deep inspiration breath-hold radiotherapy for breast cancer.Methods Forty patients with left-sided breast cancer who were treated in our hospital from May 2020 to June 2021 were randomly selected and divided into two groups. The first group's plan was a continuous semi-arc that started at 145° (±5°) and stopped at 325° (±5°). The other group's plan, defined as the tangent-arc plan, had two arcs: the first arc started at 145° (±5°) and stopped at 85° (±5°), and the second arc started at 25° (±5°) and stopped at 325° (±5°). We compared the target dose, dose in organs at risk (OARs), and treatment time between the two groups.The target dose was similar between the continuous semiarc and tangent-arc groups. The V5 of the right lung was significantly different between the two groups (Dif 5.52, 95% confidence interval 1.92-9.13, t=3.10, P=0.004), with the patients in the continuous semi-arc and tangent-arc groups having lung V5 values of (9.16±1.62)%, and (3.64±0.73)%, respectively. The maximum dose to the spinal cord was (1835.88±222.17) cGy in the continuous semi-arc group and (599.42±153.91) cGy in the tangent-arc group, yielding a significant difference between the two groups (Dif 1236.46, 95%